225k views
4 votes
With the process and explanation in details

With the process and explanation in details-example-1
User Okku
by
5.7k points

1 Answer

2 votes

Answer:

13

Explanation:

the quadratic formula will be used to solve the equation x²-3x-1=0

x = -b±√b²-4ac

2a

b= -3, a= 1, c= -1

x = --3±√3²-4*1*-1

2*1

x = 3±√9+4

2

x = 3±√13

2

x₁ = 3 + √13

2

x₂ = 3 - √13

2

x₁² + x₂² - 2x₁x₂

22 + 6√13 + 22 - 6√13 + 2

4 4

22 + 6√13 + 22 - 6√13 + 8 = 52/4 =13

4

User Chronos
by
5.5k points